A common fixed point theorem for the ψ-contractive mapping - Chen, Chi-Ming; Chang, Tong-Huei (Tamkang Journal of Mathematics, 2010)
In this paper, we shall discuss the common fixed point theorems of four single-valued functions with ψ-contractive codition in cone metric spaces.